2009
DOI: 10.1021/la9039489
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Molecular Mechanism of Anionic Dyes Adsorption onto Copper(II) Complex of Dithiocarbamate-Modified Starch

Abstract: The assembly of dyes molecules on metal-polymer complexes is of interest due to their potential applications in photovoltaic cell, separation, and wastewater treatment. In the present work, the interaction of anionic dyes (acid orange 7, acid orange 10, acid green 25, and acid red 18) with the copper(II) complex of dithiocarbamate-modified starch (DTCSCu) was investigated. The sorption studies showed that the interaction mechanism was based on chelating adsorption. The equilibrium data fitted well with Langmui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…This can deduce that attachment of sulfonic acid groups on the benzene rings (AG25, AO7) with -NH 3 + of the CAES appeared to be stronger than those on the naphthalene rings (AO10, AR18) for the high intensity of negative charge distribution. This is an interesting finding, since many authors have found similar trend that anionic dyes with sulfonic acid groups on benzene rings are easily to be adsorbed than those on naphthalene rings [39,40], but have no explanation for it. It also can be seen that AG25 which contains two sulfonic acid groups on the benzene rings suffers less sorption capacity reduction (0.801 mmol L −1 ) comparing with AO7 (1.206 mmol L −1 ) with only one sulfonic acid group on its molecule, indicates that electrostatic interaction is of importance to the sorption.…”
Section: Electrostatic Interactionmentioning
confidence: 74%
“…This can deduce that attachment of sulfonic acid groups on the benzene rings (AG25, AO7) with -NH 3 + of the CAES appeared to be stronger than those on the naphthalene rings (AO10, AR18) for the high intensity of negative charge distribution. This is an interesting finding, since many authors have found similar trend that anionic dyes with sulfonic acid groups on benzene rings are easily to be adsorbed than those on naphthalene rings [39,40], but have no explanation for it. It also can be seen that AG25 which contains two sulfonic acid groups on the benzene rings suffers less sorption capacity reduction (0.801 mmol L −1 ) comparing with AO7 (1.206 mmol L −1 ) with only one sulfonic acid group on its molecule, indicates that electrostatic interaction is of importance to the sorption.…”
Section: Electrostatic Interactionmentioning
confidence: 74%
“…To confirm these, the adsorptions of cationic compound MB and anionic compound AR18 onto pure-C, HCNP/CTS (5%), HCNP/CTS (10%), and HCNP/CTS (20%) were investigated, where cationic MB and anionic AR18 were chosen as model adsorbates because of their well-known adsorption characteristics [15,16]. Fig.…”
Section: Adsorption Performance Of Samplesmentioning
confidence: 99%
“…1). To examine the availability of HCNP samples acting as dual-use adsorbents that could be used not only for capturing cationic compound but also for adsorption of anionic compound, we selected methylene blue (MB) and acid red 18 (AR18) as the cationic and anionic model compounds [15,16], respectively, and thoroughly investigated the kinetics, equilibrium, and thermodynamics regarding the adsorptions of MB and AR18 on the HCNP samples (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, a new kind of crosslinking starch was developed as copper, nickel and chromate fixation agents [9][10][11]. However, they could not fix the vanadium (V) effectively.…”
Section: Introductionmentioning
confidence: 99%